Engaging students in writing recount text through Google Maps - Kriswanda Krishnapatria; Nur Ifah Kurniati; Hilmansyah Saefullah (Studies in English Language and Education, 2019)
Writing is undoubtedly an essential productive skill for every student in the modern era. Thus, this study investigates how students utilize the popular application of Google Maps in writing recount text and finds out their responses toward the learning activity. This research used descriptive qualitative research since it was conducted during the learning process of English subject at one high school in Karawang, Indonesia. Data sources were obtained through data triangulation consisting of observation, interviews, and documentation. This research included three phases related to checking knowledge, introducing and utilizing Google Maps in writing experiences, and finally giving assignments to students regarding their trip experience in a particular location. Based on the results of the observation, the process of teaching and learning using online Google Maps application in ELT context can enhance students’ writing as well as promote their engagement. Data from interviews shows positive responses from students in learning English through the implementation of the Google Maps application to develop their writing skills. As for the documentation, learning outcome of writing recount text stated in the lesson plan was successfully achieved through the carefully planned activities using Google Maps, and this could be seen from the students’ works. Research also reveals students are more motivated in an interactive and more fun learning process due to realistic and appealing object visualization, and not to mention its mobile practicality feature.